Firma y rúbrica de don Hernando de Vallejo en la versión poética castellana de las obras de Horacio del Ms. 7200 de la Biblioteca Nacional de España - Maestre Maestre, José María (2013)
The present paper demonstrates that the signature and paraphs appearing in the Ms. 7200 of the National Library of Spain (Madrid) are made by Don Hernando de Vallejo, chamber scribe of the Royal Council during the reigns of Philip III and Philip IV, and that their presence is due to the authentication process of the manuscript on its way into the print. This research also shows that most of Ms. 7200 was written in the seventeenth century and denies that the chamber scribe could have signed with his paraph that manuscript as the author of the Castilian poetic version of Horace’s works contained therein.
Keywords: Horacio Flaco, Quinto